The Role of Underwriting Motor Fleet Insurance - Practical Aspects - Zapart , Tomasz (Studia Oeconomica Posnaniensia, 2026)
Underwriting is one of the most important functions that characterises tic the insurance market. Underwriting policies identifies areas and types of insurance that should be developed and those products that can be developed under certain conditions. The main factor that determines the undisputed position of underwriting is experience with the poor economic condition of insurance companies caused by the excessive accumulation of losses resulting from an insufficient recognition of risk. Professional underwriting results in a profitable portfolio, ie a portfolio that meets the criteria of premium rate calculation. It enables a reduction of risk, adverse deviations from the expected results and the administrative work load. The primary purpose of underwriting is to reduce the "negative selection". Negative selection undoubtedly causes the weak financial condition of insurance companies but also badly affects a certain group of customers. As a consequence the clients who maintain appropriate safety standards still have to pay a relatively high premium as the companies compensate for the losses paid out to by customers with an adverse loss history.